Effect Of Realistic Education In Metacognition Skills Of Second Grade Intermediate Male Students In Mathematics - Mohammed Hamza, Hashim; Abed Warwar, Mohammed (Opción, 2019)
The objective of the current research was to identify the effect of the actual education model in the skills of the second grade students in mathematics. The sample consisted of (62) students. The experimental group represented (30) students and the control group (32) To determine the equivalence of the two groups in the variables (age, intelligence, past knowledge, meta-knowl- edge skills). After determining the subjects of the scientific subject to be studied during the period of application of the experiment, the behavioral goals were formulated and prepared for the teaching plans and presented to a group of experts to judge their validity and made amendments Necessary became V Ready to apply in the light of their opinions.